Kizphonic as digital multimedia online to enhance vocabulary of young learners - Lilies Youlia Friatin; Widiyaningsih Widiyaningsih (EduLite: Journal of English Education, Literature and Culture, 2018)
This study investigates the implementation of Kizphonic to enhance the vocabulary of young learners learning English as a foreign language in one of Elementary School in Ciamis, West Java. The participants in this research are all of students of the the fourth grade in one state Elementary School in Ciamis. The problem of this study is the students of the fourth grade Elementary School still in a poor of vocabulary. The aims of this study are to find out how the effect of use Kizphonic online program to enhance vocabulary of young learners and to find out students’ perceptions toward the use of Kizphonic online program during the learning process. The present study employs mixed - method study. Two instruments used in this study are observation and questionnaire. The result of the first instrument, Kizphonic as digital multimedia has a big chance on the implementation to support teachers and students in learning process, especially to enhance their vocabulary. The second instrument revealed that the majority of the students viewed that the use of Kizphonic was effective, motivating and interesting digital multimedia. It made students remember vocabulary more easily. It can be concluded that Kizphonic is able to enhance students’ motivation and enhance students’ English vocabulary.